El Sector gastronómico ancestral el “runtazo” y su potencial como atractivo turístico en la ciudad de Tunja (2020)
The article presents a proposal to improve the conditions of development of the ancestral gastronomic sector the “Runtazo”, based on the potential to become a great tourist attraction of the city of Tunja, recognizing its tradition, the value heritage and the conditions of supply and demand and thus advance processes that allow its development and turn it into a tourist attraction, driver of the local economy. Through a descriptive analytical research process, producers and consumers were surveyed on key aspects that enabled the evaluation of strongholds and deficiencies to support this proposal based on endogenous development benchmarks who consider that it is the local communities themselves who seek to enhance their capacities so that they can be used to strengthen society and their economy from the inside out and become sustainable and sustainable over time.